Effect of menstrual cycle phase and hormonal treatments on evaluation of tubal patency in baboons - Jensen, Jeffrey T. (J Med Primatol, 2017)
BACKGROUND: We evaluated whether menstrual cycle phase influences the assessment of tubal patency by hysterosalpingography (HSG) in baboons. METHODS: Retrospective analysis of baseline tubal patency studies and serum estradiol (E(2)) and progesterone (P4) values obtained from female baboons used as models for development of non‐surgical permanent contraception in women. The main outcome measure was bilateral tubal patency (BTP) in relationship with estradiol level. RESULTS: Female baboons (n = 110) underwent a single (n = 81), two (n = 26), or three (n = 3) HSG examinations. In 33/142 (23%) HSG examinations, one or both tubes showed functional occlusion (FO). The median E(2) in studies with BTP (49 pg/mL) was significantly higher than in those studies with FO (32 pg/mL, P = .005). Among 18 animals with repeat examinations where serum E(2) changed from <60 to ≥ 60 pg/mL, 13 results changed from FO to BTP (P = .0001). No sets showed a change from BTP to FO with an increase in estradiol. CONCLUSION: In baboons, functional occlusion of the fallopian tube is associated with low estradiol levels, supporting a role for estrogen‐mediated relaxation of the utero‐tubal junction.